Acetylated lignin from oil palm empty fruit bunches and its electrospun nanofibres with PVA: potential carbon fibre precursor - Harahap, Mahyuni (2023)
The electrospinning of acetylated lignin/polyvinyl alcohol (PVA) nanofibres was carried out to expand the application of lignin materials obtained from oil palm empty fruit bunches (OPEFB). Lignin was isolated by the steam explosion method and subsequently precipitated using H2SO4. Acetylated lignin was produced by mixing acetic anhydride and pyridine at a 2:1 v/v ratio. Following the acetylation process, FTIR analysis showed the absorption of the C=O carbonyl group at wavenumber 1714.6 cm-1. The chemical structures of isolated and acetylated lignin were established using 1H NMR spectral analysis, and XRD examination demonstrated their amorphous character. The electrospinning process of acetylated lignin and PVA solution was then carried out at 15 kV voltage, 0.8 mL/h flow rate, and 12 cm distance between the needle and collector. The sample exhibited electrical conductivity of 443 μS/cm and viscosity of 2.8 × 10-3 Pa s. The morphology analysis showed that there were more beads on the surface of lignin/PVA nanofibres than acetylated lignin/PVA nanofibres. In addition, acetylated lignin/PVA nanofibre was more stable than lignin/PVA. The G-band of carbonized material increased with the presence of lignin. The works presented suggest the potential of using waste materials such as OPEFB as a suitable precursor for the preparation of carbon fibre.